2022
DOI: 10.3389/fnut.2022.1002702
|View full text |Cite
|
Sign up to set email alerts
|

Association of low birthweight and small for gestational age with maternal ferritin levels: A retrospective cohort study in China

Abstract: BackgroundBirthweight have profound impacts on health status throughout lifetime, however, the relationship between maternal ferritin level in pregnancy and birthweight of the newborn remains controversial.ObjectiveThis retrospective cohort research was to analyze the association between maternal ferritin levels during pregnancy with birthweight outcomes, primarily for low birthweight (LBW) and small for gestational age (SGA).MethodsNewborns weighing lower than 2,500 grams were defined as LBW. SGA is defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Preventive strategies were divided into the 10 following categories: midwifery care, health promotion programs for smoking cessation, alcohol reduction during pregnancy, folic acid, vitamin D, iron, and zinc supplementation, a well-balanced diet, COVID-19 vaccination and cannabis use during pregnancy. The most significant and high-quality publications focusing on preventive strategies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventive strategies were divided into the 10 following categories: midwifery care, health promotion programs for smoking cessation, alcohol reduction during pregnancy, folic acid, vitamin D, iron, and zinc supplementation, a well-balanced diet, COVID-19 vaccination and cannabis use during pregnancy. The most significant and high-quality publications focusing on preventive strategies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Martínez-Galiano et al found a positive correlation between iron intake during pregnancy and SGA [ 28 ]. What is more, in a retrospective cohort study conducted in China, Tao et al found a linear dose-response relationship between ferritin levels and an increased risk of poor birthweight outcomes [ 29 ]. These data suggest that maternal ferritin level may be an additional differentiating factor for risk assessment of SGA.…”
Section: Methodsmentioning
confidence: 99%